Supporting National Transition in Myanmar with Development Assistance (Journal of International Studies, 2020)
Myanmar is undergoing significant political reforms and socio-political changes, which have been more rapid and broad than anticipated by most commentators. While ongoing reforms face significant obstacles and vested interests, and is far from assured, reform to date has already significantly altered the international relations of the state. From a development perspective, the growing international acceptability of the regime has begun to change donor attitudes, with development assistance rather than merely humanitarian aid now being discussed, and the conditionality attached to international assistance changing. This paper explores these changes in donor policies toward Myanmar, examining the prospects for development partnership with relevant government programs and agencies, and analysing the ways and sectors development assistance may be able to be used to strengthen the ongoing reform and national transition.